Comparative Study of Chinese and Foreign Cultures Based on the “Zone of Proximal Development” Theory: Taking 2012 and 2024 Editions for Grade 7 for Example - Su, Yujie; Yao, Yujun; Zhang, Yumeng; Shi, Pingping; Jin, Fangfang (International Journal of Educational Studies, 2025)
This study aims to compare and contrast the cultural content in old and new secondary English textbooks abiding by the theory of Proximal Development Zone, exploring the sustainability of cultural education within these materials. Adopting a mixed-method approach, this research analyzes the cultural themes, content presentation, and their impact on students’ cultural cognition and intercultural competence. The results indicate significant improvements in cultural diversity and intercultural education in the newer textbooks, though gaps remain between the depth of content and students’ actual understanding. Based on these findings, the paper offers several recommendations to enhance the development and teaching practices of secondary school English textbooks.